Desempeño docente en las conductas disruptivas de estudiantes con necesidades educativas especiales - Andrade Andrade, María Gabriela (2021)
The objective of this research is to analyze the effect of teaching performance in the management of disruptive behavior not associated with a disability of students in the fourth year of basic general education at Escuela de Educación Básica Particular Ab. Jaime Roldós Aguilera, to improve the classroom environment. In this sense, a bibliographic study was carried out about the main definitions and characteristics of teacher performance and disruptive behaviors as a base to develop a set of activities for the proposal. The research had a mixed approach with descriptive, documentary and field research, the latter comprises a population of 2 directors, 4 teachers, 70 students, 24 parents and 1 DECE staff. The instruments were the observation, survey and interview guide. The survey provided data on students and teachers; while the interview was applied to the manager and staff of DECE. With the information from each instrument, it is clear that teachers do not have tools to deal with disruptive behaviors that are present in the classroom. It is evident that there are no sensitization processes in the educational community. As a solution to the problem, the last chapter proposes the development of a manual of strategies for the management of disruptive behaviors in students with special educational needs.........